The Relationship between Nutritional Status and the Number of Dysmenorrhea on Childbearing-age Women - Rully prasetyo suryo nugroho; Rosalia Sri Hidayati; Indriyati . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Dysmenorrhea is estimated occured in 25% of women and about 90% occur in adolescence. Risk factors that affecting dysmenorrhea is age, nutritional status, ancestry, exercise habits, and others. Nutritional status is a matter that affects health. a less or more nutritional status has an impact on menstrual disorders including dysmenorrhea. This study aims to determine the nutritional status of the relationship with the incidence of dysmenorrhea in women of childbearing age. Methods: This study is an analytic observational study with cross-sectional approach. The samples was chosen by purposive sampling. The number of sample consist of 57 childbearing-age women who divided into 30 women with dysmenorrheal and 27 women with no dysmenorrheal. The study location taken place on linguistic and cultural department university of Sebelas Maret Surakarta. This study held on August 2014. The data were collected by direct interview and fulfilling dysmenorrheal questionnaire. The data study then being analyzed by using chi square test by using Statistical Product and Service Solution (SPSS) 17.00 for Windows. Result: The results of data analysis using chi-square technique, its obtained p = 0.031. Bivariate analysis of the relationship between nutritional status and the incidence of dysmenorrhea in women of childbearing age showed a significant relationship. Conclusion: There is a relationship between nutritional status and the number of dysmenorrheal on childbearing-age women.. Keywords: Menstruation, Dysmenorrhea, Nutritional Status